Suicide prevention education within youth work higher education: Negotiating presence and procedure - Ranahan, Patti (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
Child and youth care practitioners are likely to encounter issues of suicidality. Practitioners play an important role in the well-being of youth; thus, mental health literacy, and suicide prevention education in particular, should be an integral part of child and youth care pedagogy and curricular practices in higher education programs. With the aim of explicating a social process of learning and applying mental health literacy, this grounded theory study examined how a curriculum specifically designed for child and youth care practitioners is subsequently applied in suicide or mental health interventions. Thirteen students enrolled in youth work courses at a large university in Eastern Canada participated in the 18-month study in 2015 and 2016. Informed by critical and social literacy theories, conceptualizations of mental health literacy, and experiential pedagogy within higher education, analysis of the data identified a process of becoming and being in youth work comprising two subcategories: struggling to become a youth worker, and being a youth worker. Conditions, such as particular pedagogical strategies and specific content, served to shape and influence the process and, consequently, participants’ movement therein. The inclusion of a suicide intervention learning activity was a condition that influenced participants’ learning processes, yet also reflected a struggle with the dialectical position of presence and procedure. Recommendations and insights are discussed with the aim of enhancing pedagogical approaches to suicide intervention within child and youth care higher education programs.